Pengaruh Proses Transesterifikasi Menggunakan Katalis KOH terhadap Karakteristik Biodiesel dari Biji Sterculia Foetida Sebagai Bahan Bakar Alternatif - Dani Hari Tunggal Prasetiyo Dani; Nasrul Ilminnafik; Alief Muhammad (PERTETA, 2022)
Research on renewable energy has become an interesting topic in the era towards industry 5.0. This was because the world's energy needs continue to increase every year, especially during the industrial revolution. The use of biodiesel as an alternative fuel began to be developed along with the emergence of policies for adding biofuels to fossil fuels. Kepuh oil has the opportunity to be developed as an alternative fuel as biodiesel feedstock. This was because kepuh oil contains triglycerides. The purpose of this study was to determine the effect of catalyst concentration on density, viscosity and heating value. The catalyst used to produce biodiesel was KOH. The concentration of the catalyst used was K-0.8%; K-0.9%; K-1.0%; K-1.1% and K-1.2%. Biodiesel production was carried out at atemperature of 600C for 1 hour in the esterification and transesterification processes at the same temperature and time. The best production of kepuh biodiesel was obtained at acatalyst concentration of K-0.8% with a density value of 0.83 gr/ml, a viscosity of 2.8 cstand a heating value of 9,847 cal/gr, while the best results were obtained from mixing purediesel with kepuh biodiesel at a catalyst concentration K-0.8%. The test resulted in adensity value of 0.82 gr/ml, a viscosity of 2.24 cst, and a heating value of 10,658 cal/gr. Thehighest yield was 77.3% at 1.2% catalyst concentration